Effect of Monomeric Silicic Acid (H4SiO40) on Dispersion of a Kaolinitic Soil Clay: A dynamic Light Scattering Study - Dam, Thi Ngoc Than (ĐHQGHN, 2017)
Clay loss is the process happening frequently in the slopy hill area without the cover of vegetation. In this study, the effect of monosilic acid (MSA) on dispersion of a kaolinitic soil clay in the hilly land of Phu Tho tea trees was considered under the influence of different pH values and concentrations by the improved dynamic light scattering method. Adsorption of MSA on clay was characterized by zeta potential (ζ) and batch adsorption isotherm in a pH range of 2 to 12. At a MSA concentration range within 0 and 35 mg L-1, it was found that MSA was absorbed onto exchange sites, lowered the ζ, prohibited formation of card-house structure and finally counteracted the flocculation of clay. The most effective concentration of MSA was 5 mg L-1 at the pH range of 3.5 to 5 and electrolyte background of 0.01 molc L-1. Out of this pH range or at higher electrolyte backgrounds, clay suspension is more strongly favored or prohibited; the effect of MSA was usually hidden. Due to an ubiquitous presence in soils, it is highlighted that the impact of MSA on clay loss cannot be ignored regarding soil conservation. Fluctuated changes in adsorption and flocculation of Fe-removed clay samples for MSA have not allowed to define the role of Fe in conjunction with the relation between MSA and clay dispersibility. It should be stressed that MSA has been distributed all over assorted soil, so MSA’s impact should be considered in protecting soil.